Comparative analysis of different polynomial interpolations for implementing key management techniques in MANETs. (31st March 2022) - Monga, Chetna; Ramkumar, K.R.; Jain, Shaily
The backbreaking issue in mobile ad hoc networks (MANETs) is ensuring security which abounds due to dynamic nature and unavailability of centralised infrastructure. Due to the distributed nature of network, trading the complexity has been found so far as a natural remedy to ensure security. In order to secure MANETs, we inspect two polynomial interpolation approaches avowed as Lagrange's interpolation and other as curve fitting. The key shares are disseminated among some predefined fraction of nodes called security association members (SAMs). In order to facilitate certificate management in a versatile stance, identity (ID)-based method with polynomial-based interpolation approach is used. The new node has to fit into the parameters set by these SAMs so as to acquire the required quantity of key shares. As the key shares are transferred through error-free and error-prone channels, so the assumptions are done likewise. The analysis represents the superiority of curve fitting over Lagrange's approach as the intricacy of generating polynomial in Lagrange's approach is high than the curve fitting. The result reveals the acute accuracy of curve fitting approach along with less memory and time consumption with each order of polynomial.